Access Solar: venture proposal - Arnold, Addison, author; Figliolo, Luciana, author; Redburn, Melody, author; Sepp-Peterson, Aurora, author (Colorado State University. Libraries, 2018)
Community solar expands solar energy access by providing homeowners, renters, and businesses equal access to the economic and environmental benefits of solar energy. However, within the industry customer acquisition is a financial and operational challenge for project developers. Access Solar’s services address this by providing a turnkey solution to customer acquisition for developers. Our company streamlines the acquisition process and reaches customers through property management groups, community organizations, and electronic media marking. The market is expected to expand, with capacity experiencing a 44-fold increase from current levels by 2030. Access Solar projects sustained growth, profitability, and positive cash flow.
021 - Addie Arnold
Access Solar: everybody's energy
Keywords: solar; community solar